Determinants of household debt in Malaysia / Nazirah Aina Zaman Huri - Zaman Huri, Nazirah Aina (Faculty of Business and Management, 2020)
Household debt is the one of the important matters that need to be look seriously and done carefully. An error happens in managing household debt can lead to financial distress and bankruptcy. The aim of this study is to determine the factors of influencing rising in household debt in Malaysia between the variables which is housing price index, unemployment rate, interest rate and savings. This study is using time series data for the period of eleven years by monthly basis starting from January 2009 to March 2019. The regression analysis is employed to investigate whether the five variables construct will have a relationship with the determinants of household debts in Malaysia.